Minority voting and long-term decisions - Hans Gersbach; Theresa Fahrenberger (Center for Economic Studies and ifo Institute (CESifo), 2008)
In this paper we propose minority voting as a scheme that can partially protect individuals from the risk of repeated exploitation. We consider a committee that meets twice to decide about projects where the first-period project may have a long-lasting impact. In the first period a simple open majority voting scheme takes place. Voting splits the committee into three groups: voting winners, voting losers, and absentees. Under minority voting only voting losers keep the voting right in the second period. We show that as soon as absolute risk aversion exceeds a threshold value minority voting is superior to repeated application of the simple majority rule.
Keywords: D7; 330; voting; minority; durable decision; risk aversion; tyranny of majority rules; Abstimmungsregel; Minderheit; Wahlsystem; Zeitkonsistenz; Risikoaversion; Public Choice